Status gizi dan hubungannya dengan kejadian diare pada anak diare akut di ruang rawat inap RSUP Dr. Sardjito Yogyakarta - Astya Palupi; Hamam Hadi; Sri Suparyati Soenarto (Jurnal Gizi Klinik Indonesia, 2009)
Background: in Indonesia diarrhea is still a major cause of morbidity and mortality among children especially those under five years of age. The Household Health Survey 2000 and 2003 shows an increase of diarrhea morbidity rate from 300 to 374 per 1,000 people. At the inpatient ward of Dr. Sardjito Hospital in 2005, diarrhea was found as the major cause of patients being hospitalized. One of the causes of high diarrhea morbidity rate is poor nutritional status. In 2002, the prevalence of undernourished children in Indonesia was 27.3% and in the Province of Yogyakarta Special Territory was 11.39%. Ultimately, nutritional status and diarrhea are related to each other, which lead to very famous "vicious cycle", diarrhea causes malnutrition and malnutrition causes diarrhea. Objective: To identify relationship between nutritional status and the duration of diarrhea. Method: This observational study was conducted with retrospective cohort design using the data of medical records and surveillance of diarrhea at Dr. Sardjito Hospital from September 2005 to September 2006. Subject of the study were 138 children of 6 months to 5 years old suffering from acute diarrhea. Data analysis used Fisher's exact test and one way ANOVA.Result: The average duration of diarrhea among undernourished children was 101.0 + 28.28 hours, wasted children was 96.31 + 16.69 hours, normal nourished children was 65.06 + 6.90 hours, and well nourished children was 64.52 + 11.70 hours. There was a significant relationship between nutritional status and the duration of diarrhea (p < 0.05). Conclusion: There was a significant relationship between nutritional status and the duration of diarrhea. This means that children with poor nutritional status would likely suffer longer from diarrhea.